(untitled) (Journal of Finance, Business and Management Studies, 2024)
Technology, including the internet, phones, computers, tablets, platforms, networks, software applications, and databases, has significantly impacted our daily lives. The integration of e-commerce platforms in rural agricultural sectors has opened new opportunities for farmers and producers to reach wider markets. These platforms can facilitate growth, efficiency, and market access for rural farmers. As rural revitalization progresses, e-commerce can help agriculture development through diversification, intelligent agriculture, and e-commerce trading platforms. These platforms have the potential to revolutionize traditional farming by creating direct links between farmers and buyers. This paper aims to study the development strategy of e-commerce in rural areas, focusing on marketing status, problems, and specific development strategies, to promote the development of e-commerce in rural areas under the background of rural revitalization.